PENENTUAN MEDIA PROMOSI STT WASTUKANCANA PURWAKARTA MENGGUNAKAN METODE WEIGHTED AGGREGATED SUM PRODUCT ASSESMENT (WASPAS) - Intan Nopita; Muhammad Rafi Muttaqin; Nurfitriansyah (Program Studi Informatika Universitas Teknologi Sumbawa, 2022)
Promotion is an element used to informand persuade the market about a new product or service to the companythrough an advertisement. However, the large selection of promotional media at this time makes us required to continue to make decisions properly, precisely and also quickly, and accountable. This study aims to create a decision support system in choosing promotional media at the Wastukancana Purwakarta Cpllege of Teknology (STT) with the Weighted Aggregated Sum Product Assesment method. Where the alternatives and criteria have been determind by the Wastukancana STT Promotion Team. There are (five) criteria that have been determined, namely financing,completeness of information, promotional content, reac,and flexibility of acces. As well as for alternatives, namely brochures,banner, socialization,social media and websites. The software didevelopment method used is waterfaal. This application is buit using PHP Codeigniter and MYSQL, then the testing method uses Black Box Testing. The calculation result put social media as the most recommended alternative promotional media.